APPLYING CLEANER PRODUCTION AND OPTIMISING HEAT PROCESS OPERATIONS IN DAIRY PROCESSING PLANTS – A REVIEW - Muredzi, P. (European Scientific Journal, ESJ, 2015)
It is often claimed that Cleaner Production techniques do not yet exist or that, if they do, they are already patented and can be obtained only through expensive licenses. Neither statement is true . Applying cleaner production and optimising heat process operations in dairy processing plants is a critical and topical issue in today’s global food industry hence the appropriateness of this review article. This review paper discusses issues of cleaner production for the dairy industry, the methodologies and approaches in optimising heat processes. The paper also identifies the cleaner production opportunities for production processes, cites a case study of pasteurization and gives appropriate recommendations for dairy plants.